2020
DOI: 10.1289/ehp6263
|View full text |Cite
|
Sign up to set email alerts
|

Locus-Specific Differential DNA Methylation and Urinary Arsenic: An Epigenome-Wide Association Study in Blood among Adults with Low-to-Moderate Arsenic Exposure

Abstract: BACKGROUND: Chronic exposure to arsenic (As), a human toxicant and carcinogen, remains a global public health problem. Health risks persist after As exposure has ended, suggesting epigenetic dysregulation as a mechanistic link between exposure and health outcomes. OBJECTIVES: We investigated the association between total urinary As and locus-specific DNA methylation in the Strong Heart Study, a cohort of American Indian adults with low-to-moderate As exposure [total urinary As, mean ð±SDÞ lg=g creatinine: 11.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 81 publications
3
33
0
Order By: Relevance
“…HNRNPUL1 , annotated to the DVP cg26384602, was also found to be differentially methylated with maternal urinary arsenic in cord blood in a Taiwanese birth cohort [ 17 ]. We also compared our DMPs and DVPs to all nominally significant DMPs previously associated with urinary arsenic levels among adults in the US ( p < 0.05) [ 9 ]. Notably, HDAC4 included 38 DMPs, SNTG2 included 9 DMPs, and TOLLIP included 8 DMPs identified by Bozack et al in the Strong Heart Study, a cohort of American Indian adults from the Great Plains and the Southwest [ 9 ] ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…HNRNPUL1 , annotated to the DVP cg26384602, was also found to be differentially methylated with maternal urinary arsenic in cord blood in a Taiwanese birth cohort [ 17 ]. We also compared our DMPs and DVPs to all nominally significant DMPs previously associated with urinary arsenic levels among adults in the US ( p < 0.05) [ 9 ]. Notably, HDAC4 included 38 DMPs, SNTG2 included 9 DMPs, and TOLLIP included 8 DMPs identified by Bozack et al in the Strong Heart Study, a cohort of American Indian adults from the Great Plains and the Southwest [ 9 ] ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…A greater number of DMPs was also identified among males in an EWAS of prenatal arsenic exposure on DNAm measured at age 9 in Bangladesh ( N = 113): 9, 57, and 15 CpGs were associated with exposure among children overall, males, and females, respectively ( FDR < 0.05), with no overlap between CpGs identified in sex-stratified analyses [ 14 ]. However, in an EWAS of arsenic exposure in the Strong Heart Study ( N = 2,325), substantial sex-specific effects in stratified analyses were not observed with all FDR-significant CpGs achieving nominal significance in sex-stratified analyses ( p < 0.05) [ 9 ]. Further, in our study, there is insufficient evidence to conclude that prenatal exposure is associated with sex in the Chile study’s datasets (Pearson’s chi-squared test p = 1, 0.88 in the PBMC and the buccal studies, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations